Barriers to Meeting Community Needs in New York State during COVID-19: Results From a Pilot Survey of Nongovernmental Population and Community Health Professionals. Issue 2 (March 2023) - Schiavo, Renata; Arana, Mayela; Levy, Nicole; Grijalva, Yesenia; Ravenhall, Sarah; DiManno, Margaret; Murrman, Marita
Capacity building and training help empower the community and population health organizations to partner with local health departments and collaboratively design multisectoral interventions that account for the complexity of public health and health promotion challenges in the era of COVID-19 and beyond. Ideally, training programs should be informed by an understanding of the needs and priorities of the professionals for whom they are intended. This brief report focuses on the results of a pilot online survey conducted as part of a larger pilot study by the New York State Association of County Health Officials and the Region 2 Public Health Training Center among population and community health professionals ( n = 27) from four counties in New York State during the COVID-19 pandemic. Survey participants included a diverse group of staff members from various large and small nonprofit organizations, federally qualified health centers, academic institutions, hospitals, and insurers. Survey findings provide preliminary insights into the extent to which these organizations have been involved in the COVID-19 response in partnership with LHDs, barriers they faced in responding to the needs of the populations they serve and adjusting their work routines/operations to COVID-19 guidelines, and their top emerging organizational and training needs. Lessons learned from conducting an online survey during a public health emergency and implications for future training interventions for population and community health professionals are also discussed within the context of promoting multisectoral collaboration with local health departments, solving complex public health problems, and advancing health equity.